Cold Tropical Pacific Sea Surface Temperatures During the Late Sixteenth‐Century North American Megadrought. Issue 20 (16th October 2018) - Cook, Benjamin I.; Williams, A. Park; Smerdon, Jason E.; Palmer, Jonathan G.; Cook, Edward R.; Stahle, David W.; Coats, Sloan
Abstract: The late 16th‐century North American megadrought was notable for its persistence, extent, intensity, and occurrence after the main interval of megadrought activity during the Medieval Climate Anomaly. Forcing from sea surface temperatures (SSTs) in the tropical Pacific is considered a possible driver of megadroughts, and we investigate this hypothesis for the late 16th‐century event using two new 600‐year long hydroclimate field reconstructions from Mexico and Australia. Areas represented by these reconstructions have strong teleconnections to tropical Pacific SSTs, evidenced by the leading principal component in each region explaining ∼40% of local hydroclimate variability and correlating significantly with the boreal winter (December‐January‐February) NINO 3.4 index. Using these two principal components as predictors, we develop a skillful reconstruction of the December‐January‐February NINO 3.4 index. The reconstruction reveals that the late 16th‐century megadrought likely occurred during one of the most persistent and intense periods of cold tropical Pacific SST anomalies of the last 600 years (1566–1590 C.E.; median NINO 3.4 = −0.79 K). This anomalously cold period coincided with a major filling episode for Kati Thanda‐Lake Eyre in Australia, a hydroclimate response dynamically consistent with the reconstructed SST state. These results offer new evidence that tropical Pacific forcing was an important driver of the late 16th‐century North American megadrought over the Southwest and Mexico, highlighting the large amplitude of natural variability that can occur within the climate system. Key Points: One of the most severe megadroughts in North America occurred in the late 16th‐century We show this event occurred during a 25‐year cold period in the tropical Pacific Ocean This provides evidence linking ocean forcing and megadroughts outside the Medieval Climate Anomaly